Analisa Usaha Tani terhadap Aplikasi Pupuk Majemuk Cair pada Tanaman Jagung Manis - Oviyanti Mulyani; Emma Trinurani Sofyan; Rija Sudirja; Yulianti Machfud; Benny Joy (Fakultas Pertanian Universitas Padjadjaran, 2019)
Analysis of the farming system is an applied science which concerns on how to use resources efficiently and effectively in agricultural business in order to get maximum results. In this analysis, one of the important aspects on agricultural production is fertilizer. Liquid compound fertilizer is a fertilizer with several advantages such as simple application, complete and balanced required nutrients, labour and time efficient, and easy to procure and store. The purpose of this study was to determine the analysis of farming system on the application of liquid compound fertilizer on sweet corn. This experiment used a Randomized Block Design (RBD) consisted of 10 treatments (8 treatments of liquid fertilizer doses, one treatment of fertilizer dosage recommendations for NPK and one control (without fertilizer)). Each treatment was repeated three times, with the total of 30 experimental plots. The results of this experiment were the application of compound liquid fertilizer provides a high relative value of agronomic efficiency and profits on corn. The treatment of 1 ¼ NPK liquid fertilizer dose gave higher RAE, R/C and B/C values compared to the control. NPK liquid fertilizer has a significant effect on the variables of soil (pH, N, P and K content) and yield components (N, P and K uptake). In general, the use of NPK liquid fertilizer can significantly increase the yield, with the highest yield on 1 ¾ dose and the yield of corn plants (18,329 kg/ha).